Pengaruh Latihan Rope Skipping Terhadap Peningkatan Kekuatan Otot Tungkai Pada Pemain Bulutangkis Di Pb Tanker Kartasura - Apdanita, Rani, Dwi Kurniawati, SSt.FT (2017)
Background : In badminton players must have a good physical condition. The players are required to perform complex ments such as sprinting, stopping abruptly and soon moved again, leaping motion, reaching, twisting the body quickly and perform stride without ever losing the balance of the body. The motion requires the player to review the Good muscle strength.Objective: To Determine the effect of Rope skipping exercises to increase of leg muscle strength in badminton players in PB Tanker Kartasura.Methods: This study is a true experimental study with pre-post test with control group design. Sampels of this study were 20 people who divided into two groups : treatment group (Rope skipping exercise) and control group (without treatment). The study asconducted over 4 weeks, the frequency of exercise 3 times a week. 2Measurements of muscle strength using Sphygmomamometer Modified Test (MST). Data analysis using Wilcoxon test and Mann-Whitney test.Result : Based on the statistical results to test the effect before and after practice Rope skipping obtained p-value 0.005 on the right leg and 0.005 on the left leg means that there is the effect of Rope skipping exercises to increase leg muscle strength. While the influence of different test obtained p-value 0.008 on the right leg and 0.021 on the left leg, so it can be concluded that there are differences in the increase in leg muscle strength badminton players in the treatment group or the control group.